Development and characterization of carbon fiber from polyacrylonitrile precursor - 363579 Muhammad Syukri Abd. Rahman (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Gas)) - Universiti Teknologi Malaysia, 2006